Comparison of biogas recovery from MSW using different aerobic-anaerobic operation modes. (October 2016) - Xu, Qiyong; Tian, Ying; Kim, Hwidong; Ko, Jae Hac
Highlights: Aerobic MSW pretreatment reduced the acidic inhibition on methane generation. COD & VFA of leachate were greatly decreased in aerobically treated bioreactors. A gradually-reduced aeration mode improved methane recovery from MSW. Abstract: Aeration pretreatment was demonstrated as an efficient technology to promote methane recovery from a bioreactor landfill with high food waste content. In this study, a short-term experiment was conducted to investigate the effects of aerobic-anaerobic operation modes on biogas recovery. Three landfill-simulated columns (anaerobic control (A1), a constant aeration (C1) and a gradually reduced aeration (C2)) were constructed and operated for 130 days. The aeration frequency was adjusted by oxygen consumption in an aerated MSW landfill. After aerobic pretreatment was halted, the methanogenic phase was rapidly developed in both the C1 and C2 columns, reducing the volatile fatty acid (VFA) concentrations and increasing pH. The methane volumes per dry MSW produced from the C1 and C2 columns were approximately 62 L/kgVS and 75 L/kgVS, respectively, while methane produced from the A1 column was almost negligible. The result clearly showed that aerobic pretreatment with gradual reduction of aeration rates could not only improve methane recovery from waste decomposition, but also enhance leachate COD and VFA removal.